Drought and vulnerability of livestock in India - Akter, S.; Farrington, John; Deshingkar, P.; Rao, L.; Sharma, P.; Freeman, H.A.; Reddy, J. (International Livestock Research Institute, 2008)
This study examines the dynamics of livestock keeping in recent years when occurrence of droughts was severe; the function of livestock in reducing the vulnerability to shocks and stresses to which the poor are exposed; and the relationship between migration and aspects of livestock keeping in the context of drought and vulnerability. The discussion paper is organized as follows: Following the executive summary, Section 2 introduces the paper giving its background. Section 3 describes the methodology. Section 4 presents an overview of livestock keeping and poverty. Section 5 describes the dynamics of livestock keeping in two subsections. Section 6 analyzes livestock sales due to major expenses in three years. The relationship between migration income and livestock keeping is examined in Section 7. The paper concludes with Section 8, where implications are discussed. Questionnaire for 2005 panel re-survey and qualitative assessment of the impact of commercial poultry farms on backyard poultry production and additional tabulation are included in the appendices. The report is primarily based on the 2005 re-survey data supplemented by data collected from 2001-02 survey as well as qualitative method.